Examining The Potential of Cash Waqf and Development Model - Madani, Rahma Insan; Nurhidayati, Nurhidayati; Thomafy, Khoiriyah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This research aims to determine the potential of cash waqf and its development model, so research. This research uses the literature study method supported by previous research data. The results of this study reveal that the potential and development model of cash waqf has not been well realized. This research has the advantages of waqf: Continuous reward as long as the waqf object is still being utilized even though the waqf has passed away. Continuous benefits in various types of goodness and not interrupted by the transfer of ownership. As a productive investment because cash waqf can be invested in Sharia-compliant financial instruments, which can generate returns that can be used for charitable purposes. However, implementing cash waqf in Indonesia is still far from its potential. Various regulations have been established to accommodate cash waqf, but its collection and utilization have not reached the expected potential. This article discusses the current cash waqf implementation model and highlights the need for more effective mechanisms, especially for millennials. This research also explores philanthropy and social fund management trends, providing insight into the potential of cash waqf and its growth models.